Citizen criminality assessment in lima city using the grey clustering method - Delgado, Alexi (2017)
Citizen criminality has become an important social problem in Lima city, due to the fact that the number of crimes has increased. In this study, we conducted a citizen criminality assessment using the grey clustering method, which is based on grey systems theory. The case study was conducted on 32 districts from Lima, Peru. Consequently, a map on the citizen criminality situation was obtained. The results revealed that the more insecure districts were San Juan de Lurigancho, Los Olivos, and Cercado de Lima; and the less insecure districts were Ancón, Surquillo, and Lince. The study results could help to the central and district government to make the best decision on the citizen criminality problem. The grey clustering method showed interesting results and could be applied to other social problems, as this method considers the uncertainty within its analysis.